(untitled) (TAJ: Journal of Teachers Association, 2018)
An intensive care unit (ICU) is a special part of hospital where expertise medical and nursing care has been provided along with monitoring and organ support. An analysis of first 300 patients was carried out to investigate retrospective review of data from ICU of Rajshahi Medical College Hospital (RMCH) Rajshahi. During this study period, the frequency of admission into ICU was more from medical discipline (49%%) than other disciplines like surgical (42.33%), gynaecological, obstetric and other disciplines (8.66%%). The incidence of survival was 56.69% from surgical, 44.21% from medical and 38.46% from gynaecological and other disciplines and mortality was 35.94%, 53.59% and 10.45% respectively. Occurrence of total ventilatory support provided in all disciplines was 68%. In other studies it was found that the ICU mortality varies between 15% to 44% depending on various factors like age, severity of diseases, length of stay and organizational capability of the ICU. The most prevalence of diseases admitted into this ICU was medical diseases, which were 25% and second prevalent diseases were head injury 20.66%. The incidence of immediate mortality within 24 hours was 42 % TAJ 2012; 25: 8-12